Physical literacy among older adults: a scoping review of definition, attributes, contributing factors, consequences and interventions - Yu, Yawei; Duan, Yu; Guo, Hong; Chen, Yiping (Frontiers in Public Health, 2025)
BackgroundPhysical literacy (PL) is increasingly recognized as a foundational component of lifelong physical activity participation and healthy aging. However, research on PL in older adults remains scattered and lacks synthesis across domains.ObjectiveTo systematically map the current research landscape on physical literacy in older adults, including its definitions, core attributes, contributing factors, health-related outcomes, and intervention practices.MethodSix databases (PubMed, Web of Science, Embase, CINAHL, SPORTDiscus, and PsycINFO) were searched from inception to May 2025. Additional grey literature was identified through Google Scholar and reference screening. Adopted Arksey and O′Malley’s five-stage methodological framework, two reviewers independently screened and extracted data focusing on definitions, attributes, antecedents, consequences, and interventions related to PL in older adults. Findings were synthesized using Braun and Clarke’s descriptive thematic analysis approach.ResultsEighteen studies were included, which were published between 2019 and 2025, spanning medicine, psychology, and social sciences. The concept of PL among older adults did not have a consolidated definition but was identified through five defining attributes: Physical competence, Motivation and confidence, Knowledge and understanding, Affective and cognitive engagement and Environmental and social interaction. Influencing factors clustered into four categories: biomedical, psychosocial and behavioral habits, sociocultural environment, and education and early experiences. PL was positively associated with physical and mental health, willingness to engage in physical activity, successful aging, and public health outcomes. Intervention strategies included education-based programs, functional exercise training, dance, and exergaming.ConclusionPhysical literacy is essential for supporting active aging. Standardized assessment tools and integrated interventions are needed to enhance PL among older adults. Future efforts should build upon the attributes of PL among older adults to develop or refine multidimensional assessment tools specifically designed for older adults, ensuring their cultural relevance and practical applicability.